A3-4: Implementing a Pragmatic Clinical Trial: Lessons Learned about Embedded Research - Kindler, Lindsay (Clin Med Res, 2014)
BACKGROUND/AIMS: Pragmatic trials are fostering a paradigm shift to increasingly embed research into healthcare settings. Pragmatic trials test interventions in real world settings representative of those targeted for dissemination to promote robust, sustainable changes within the health care system. Kaiser Permanente’s Center for Health Research, is conducting a pragmatic trial to test the effectiveness of teaching pain self-management skills using interdisciplinary teams within primary care in three Kaiser regions. Implementation requires a pragmatic approach to create a working relationship between health system leaders and the research team. We present lessons learned during our preparatory year in which we partnered with health systems to build an embedded research infrastructure for the study. METHODS: In accordance with a pragmatic approach, we used the Rapid Assessment Process (RAP) whereby the fieldwork team gathers and analyzes information quickly in the form of journal entries and detailed meeting minutes following stakeholder encounters and regular team meetings to document the emerging collective understanding of stakeholders’ expressed concerns and informational needs. This approach allows for iterative feedback from operational stakeholders and accommodates quick trial modifications. RESULTS: Using RAP to systematically identify lessons learned, several guiding principles surfaced for successfully embedding research into a healthcare system. The study foundation must come from a need identified by the health system, not the research team. Study outcomes must have obvious utility to operational leaders and practicing providers. Health plan administrators and clinicians have pre-existing ideas of research that necessitate ongoing education and dialogue to address concerns. Using a framework of change native to the health system promotes navigation of potentially disruptive change. Given rapid changes within health systems, the research team must be aware of competing contextual factors. Finally, a true health system/research partnership when staffing the intervention facilitates sustainability of intervention related services. CONCLUSIONS: A pragmatic trial approach, although better suited for embedded research in the healthcare system, presents challenges not typically encountered in standard explanatory/efficacy trials. Lessons learned by this team that accommodate both healthcare operations and research can promote embedded research in other health settings.